A study of a PERMA-based positive psychological intervention programme in subthreshold depressed patients with newly diagnosed breast cancer: formulation and application - Wang, Deju; Li, Bin; Xin, Hongmei; Wu, Xiaofei; Xia, Jieqiong (Frontiers in Psychology, 2024)
Background: Depression seriously affects the quality of life of breast cancer patients and even hinders treatment and recovery after diagnosis. Subthreshold depression should be worthy of attention, and the risk of subthreshold depression developing into depression increases if timely intervention is not available. However, there is limited research on interventions for subthreshold depression, especially for newly diagnosed breast cancer patients.Objective: Exploring the efficacy of a PERMA-based positive psychological intervention programme in newly diagnosed breast cancer patients with subthreshold depression.We constructed and revised the intervention programme using PERMA as a framework, a literature review, the Delphi method and the expert discussion method.Then we selected 84 newly diagnosed breast cancer patients for a randomised controlled trial. The control group received conventional care , and the observation group received a PERMA-based positive psychological intervention programme. Patient data were collected before and after the intervention, and the dataset consisted of patient responses to general information, the Depression Screening Scale (CES-D), the Hamilton Depression Inventory (HAMD-17), and the Questionnaire on Psychosocial Adjustment in Breast Cancer Patients.Results: A total of 79 patients completed the study (38 patients in the observation group and 41 patients in the control group), and before the intervention, there were no statistical differences in the comparison of general information, subthreshold depression scores, and psychosocial adaptation scores between the two groups (P> 0.05).After the intervention, the subthreshold depression (CES-D and HAMD-17 scores) scores of the observation group were lower than those of the control group (P< 0.01), and the psychosocial adaptation scores were significantly higher than those of the control group (P< 0.01).A positive psychological intervention programme using PERMA as a framework was more effective in reducing subthreshold depression levels and promoting levels of psychosocial adjustment in newly diagnosed breast cancer patients.Implications for Practice: Based on a positive psychology perspective, interventions are implemented for newly diagnosed breast cancer patients to reduce their subthreshold depression levels and prevent them from developing more severe depression. Helping them to gradually adapt to their new identity and treatment process in a positive way during the most difficult period. This is a new and significant endeavour.